Wednesday

July 30, 2014

July 30, 2014

Posted by **jj reddick** on Sunday, October 24, 2010 at 5:53pm.

- trig -
**bobpursley**, Sunday, October 24, 2010 at 5:55pm(1+cosx)/(1-cosX)*secx/secx

(secx+1)/(secx-1)

**Related Questions**

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Pre Calculus - Having trouble verifying this identity... cscxtanx + secx= 2cosx ...

precal - 1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-...

math - 1. (sinx/cscx)+(cosx/secx)=1 2. (1/sinxcosx)-(cosx/sinx)=tanx 3. (1/1+cos...

Simplifying with Trigonometry Identities - Hi, I am a senior in High School ...

Pre-Calculus - How do you verify: 1.) sinxcosx+sinx^3secx=tanx 2.) (secx+tanx)/(...

trigonometry - how do i simplify (secx - cosx) / sinx? i tried splitting the ...

trig - How do I prove these trig identities? secx-cosx/tanx =sinx And 1+sinx/...

Trig - If secx = 8 and -pi/2 < x < 0, find the exact value of sin2x Use ...

Trig - Prove: (cotx sinx)(secx-cosx)=sin^2(X)